Methanol extract and fraction of Anchomanes difformis root tuber modulate liver mitochondrial membrane permeability transition pore opening in rats - Oludele Olanlokun; Kemi Oloke; Olufunso Olorunsogo (Mashhad University of Medical Sciences, 2020)
Objective: Extracts of Anchomanes difformis (AD) are used in folkloric medicine to treat several diseases and infections. However, their roles in mitochondrial permeability transition pore opening are not known. Material and Methods: The viability of mitochondria isolated from Wistar rat liver used in this experiment, was assessed by monitoring their swelling amplitude in the absence of calcium and reversal of calcium-induced pore opening by spermine. The effects of methanol extract and fraction of A. difformis (MEAD and MFAD, respectively) on Mitochondrial Membrane Permeability Transition (MMPT) pore opening, ATPase activity, cytochrome c release and ferrous-induced lipid peroxidation were assessed spectrophotometrically. Phytochemical constituents of MEAD and MFAD were assessed using Gas Chromatography- Mass Spectrometry (GC-MS). Results: The MEAD (10, 20, 40 and 80 μg/ ml) had no effect on MMPT pore opening in the absence of Ca2+, whereas MFAD at 80 μg/ml had a large amplitude pore opening effect. Both MEAD and MFAD reversed Ca2+‌‌-induced swelling with inhibition values of 18, 21, 24, 23% (for MEAD) and 41, 36, 35, and 26% (for MFAD) at 10, 20, 40 and 80 μg/ml, respectively. MFAD significantly enhanced F1F0 ATPase activity and caused cytochrome c release. Both MEAD and MFAD significantly inhibited ferrous-induced lipid peroxidation by 33.0, 64.0, 66, and 75% (for MEAD) and 24, 25, 30, and 45% (for MFAD), respectively. The GC-MS results revealed the presence of squalene as one of the major constituents of MEAD. Conclusion: These findings suggest that MFAD can be used to induce cell death via mitochondrial permeability transition in isolated rat liver. Inhibition of lipid peroxidation by MEAD and MFAD showed that the pore opening effect of the extract and fraction was not mediated via peroxidation of mitochondrial membrane lipids.